Patient experience in cystic fibrosis care: Development of a disease-specific questionnaire. (June 2015) - Stahl, Katja; Steinkamp, Gratiana; Ullrich, Gerald; Schulz, Wolfgang; van Koningsbruggen-Rietschel, Silke; Heuer, Hans-Eberhard; Ellemunter, Helmut; Schwarz, Carsten
Objectives: The aim of this study was to develop valid and reliable disease-specific questionnaires for adult patients with cystic fibrosis and for parents of minors with cystic fibrosis for assessing patient experience with cystic fibrosis care. Methods: The pilot versions of the questionnaires were developed based on a literature review, interviews with health professionals and focus groups. A postal survey with two reminders was conducted in 56 German cystic fibrosis centres recruiting 2874 participants. Psychometric evaluation was done via exploratory factor analysis and reliability and regression analysis. The questionnaires' ability to differentiate between subgroups and between cystic fibrosis centres was evaluated. Results: Response rates were 74% for both adult patients and parents. Ten factors were extracted for both the adult and the parents' models (Cronbach's alpha between 0.6 and 0.9), explaining 50% and 48% of the variance, respectively. The factors organisation & access and the doctor–patient/parent-interaction had the highest relevance for a good overall care experience. The questionnaires were able to distinguish between different cystic fibrosis centres. Discussion: The questionnaires are well suited for use in internal and external quality management of cystic fibrosis care due to their good psychometric properties, the ability to differentiate between centres and its practicability.